2005
DOI: 10.1002/polb.20646
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystalline complexes of an azo‐containing surfactomesogen with oppositely charged polyelectrolytes

Abstract: A triethyl-ammonium functionalized 4-nitro-4 0 -alkoxy azobenzene mesogen with a 10-carbon spacer (azo10Q, a ' 'surfactomesogen' ') was complexed in equimolar proportions to a variety of oppositely charged polyelectrolytes, and studied by differential scanning calorimetry (DSC), polarizing optical microscopy, and X-ray diffraction. The complexation generates a single-layer smectic A mesophase over a very wide temperature range from a surfactomesogen that, alone, melts directly to the isotropic phase. The clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 49 publications
3
20
0
Order By: Relevance
“…For example, vertical structure resolution within LC films could be obtained from films on tailored reflecting substrates [ 52 ] using temperature controlled setups. One the other hand, extension of LC-approved SM methods to other LC materials and configurations, such as free standing LC films [ 70 ] and single-layer smectics [ 71 ], is featured to extend the insight on such materials. Moreover, further development of SM methods will increase the research possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vertical structure resolution within LC films could be obtained from films on tailored reflecting substrates [ 52 ] using temperature controlled setups. One the other hand, extension of LC-approved SM methods to other LC materials and configurations, such as free standing LC films [ 70 ] and single-layer smectics [ 71 ], is featured to extend the insight on such materials. Moreover, further development of SM methods will increase the research possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…[25] The latter pattern, reported a number of times in the literature, is generally ascribed to extinction of the first-order peak by an additional plane of symmetry in the electron density profile along the lamellar normal. [18,25,[33][34][35][36][37][38][39] Assuming that the most intense diffraction peak for the polar-tailed complexes is indeed a second-order reflection, it was observed that all of the liquid crystalline complexes had a periodicity close to a single extended molecular length of the repeat unit (considering that the ion pairs can be arranged either parallel or perpendicular to the molecular long axis), thus indicating effectively single-layer SmA phases.…”
Section: Methodsmentioning
confidence: 99%
“…[25] Finally, it is worth mentioning that the present study was inspired by some apparent irreproducibility in the intensity pattern of the low angle XRD region during initial investigations of O 2 N-O10Q/PSS. [18,25] Complexes Exposed to H 2 O Although the complexes are insoluble in water, their ion content can lead to water absorption. The equilibrium absorption in the complexes exposed to 100% RH, measured gravimetrically over a period of 2 weeks and generally found to be constant within a day, was found to range from 15 to 25 wt.-%, corresponding to 7-10 H 2 O molecules per repeat unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting materials are highly structured and show a variety of liquid crystalline phases. [26][27][28][29][30][31][32] When the complexes are processed from organic solvent to thin films, and then exposed to light, they can be used to create surface relief gratings, 28,30 generate optical anisotropy, 29 or can be applied as aligning layers for liquid crystals. 28 One promising PSCs application is the development of non-viral gene delivery vectors based on DNA.…”
Section: Introductionmentioning
confidence: 99%